T.S.Eliot as a Pentecostal Playwright: Towards a Pneumatic Poetic - Crace, Benjamin (2021)
Following the postmodern, “spiritual” turn and the growing influence of experience-oriented, Pentecostalized Christianity, this paper seeks to build a pneumatic poetic from philosophical/theological foundations all the way through to the literary with T.S. Eliot as an interlocutor. Aspects of Eliot’s thinking are shown to align with recent trends in theology and cosmology. Moving from hermeneutic to poetic via the Scriptures, I argue Eliot’s concerns with language and experience cohere with a pneumatic orientation that gets worked out in his drama. The resultant pneumatic poetic is used to manifest that orientation in his last play The Elder Statesman.